THE CONSTRUCTIONAL SUBSCHEME [[X] PREP N] IN BRAZILIAN PORTUGUESE: A CONSTRUCTIONAL APPROACH - Souza, Edson Rosa Francisco de [UNESP]; Rezende, Jordan Faria de [UNESP]; Salton, Mariane [UNESP] (Centro Univ Uniabeu, 2024)
This paper aims at analyzing, based on Scaldelai (2016, 2017, 2020) and ScaldelaiSalles and Souza (2020), the intensification constructional subschema [[X] Prep N] in Brazilian Portuguese, which instantiates various intensifying microconstructions, such as pra cacete, do (TRAUGOTT and TROUSDALE, 2013; BYBEE, 2010), considering the properties of schematicity, compositionality, and productivity, which are fundamental for the formation and conventionalization of these expressions. According to the authors, these constructions serve to intensify or exaggerate aspects of something. Using the Corpus of Portuguese (DAVIES and FERREIRA, 2006), which contains billions of words, this study seeks to inventory and describe the microconstructions derived from the [[X] Prep N] subschema, distinguishing them from other simple constructions, such as muito and demais. The data indicate that these expressions convey meanings such as: (i) referentiality, when the nominal head refers to entities in the world; (ii) quantification, when it quantifies individuals or objects, as in gente pra cachorro; (iii) intensification, when it modifies verbs, adjectives, or adverbs, as in correu pra caramba. The subschema proves to be highly productive in Brazilian Portuguese, fostering the creation of new constructional patterns.
Keywords: Intensification; Quantification; Constructional Approach